State, Problems and Needs for Research of Professional Nurse at Faculty of Medicine, Prince of Songkla University - Sangmanee, Watcharee; Kaewvichit, Namtip; Tohteng, Sumairoh (Princess of Naradhiwas University Journal, 2021)
This descriptive research study aimed to study state problems and needs for research and to compare opinions and guidelines for promoting institutional research of professional nurse at Faculty of Medicine, Prince of Songkla University. The samples of this study were 340 supporting staffs, professional nurse at Faculty of Medicine, Prince of Songkla University, randomized sampling by multi-stages. The data were collected from June 2018 to May 2019. The research instruments were questionnaires from Worapon Wilaem et al. which were tested its reliability with Cornbrash’s Alpha coefficient State (0.91) Problems (0.93) and Needs (0.90). Data were analyzed through descriptive statistics including percentage, mean, and standard deviation as well as inferential statistics including statistics Independent-Samples T Test, One-way Analysis of Variance (One-way Anova). The results of this study showed that the state of nurse’ evaluation was at a few level knowledge (Mean = 2.28, S.D. = 0.96) and skill (Mean = 1.98, S.D. = 1.24). Problems of time was at a high level (Mean = 3.50, S.D. = 1.20). Needs of motivation in research was the highest (Mean = 3.23, S.D. = 1.15). The evaluation of supporting factors showed the resources for document research was at a high level (Mean = 3.52, S.D. = 0.96). Problems of budgets (Mean = 3.06, S.D. = 1.00) and needs of resources for document research (Mean = 3.23, S.D. = 1.15) were the highest. For comparing the opinions, the analysis showed that when classified by personal types, it did not show statistically significance. When classified by academic position, it showed statistically significance at 0.01 level.